(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Hypoglycemia is the commonest medical emergency in diabetic patients. It is also the most important limiting factor in intensive control of diabetes. To find out the frequency of hypoglycemia in Medical Emergency of BIRDEM General Hospital. Materials and methods: This cross sectional observational study was done at the Medical Emergency Department of BIRDEM General Hospital, Dhaka, during the period of March, 2015 to November, 2015. Among the patients attending the emergency department, hypoglycemic patients were identified. Socio-demographic, clinical and biochemical data was collected from these patients. Statistical analysis was done with SPSS version 23.0. Results: Among the 20564 patients attending the medical emergency department in the specified time period, 577 (2.8%) patients had hypoglycemia. More than half (50.09%) patients were found mild impairment of consciousness (GCS >12). Conclusion: The present study found that frequency of hypoglycemia in patients attending in Medical Emergency Department of BIRDEM General Hospital was 2.80%. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 8-11